2015
DOI: 10.14214/sf.1301
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization increased growth of Scots pine and financial performance of forest management in a drained peatland in Finland

Abstract: • All fertilizers containing phosphorus and potassium improved the P and K status and the stem growth of Scots pine still 26 years from application.• Wood ash, containing more nutrients than other fertilizers, gave the strongest stand growth response and the highest net present value.• Ash fertilizer treatment outperformed other fertilizer treatments and control in net present value, regardless of the applied discount rate, 3%, 4% or 5%. AbstractThe long-term effects of fertilization on the needle nutrient con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
(41 reference statements)
1
17
1
Order By: Relevance
“…The Kannus site was a typical target for ash fertilisation in terms of high N content in peat and deficiency of P and K in the tree stand. The average growth of 2.9 m 2 ha -1 a -1 on control plots during the 15-year study period was similar to that reported by Moilanen et al (2015) for an unfertilized stand. Loose ash increased stem volume growth 2.2-fold, and granulated ash and PK fertiliser 1.7-1.8-fold compared to the control over the 15 years.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The Kannus site was a typical target for ash fertilisation in terms of high N content in peat and deficiency of P and K in the tree stand. The average growth of 2.9 m 2 ha -1 a -1 on control plots during the 15-year study period was similar to that reported by Moilanen et al (2015) for an unfertilized stand. Loose ash increased stem volume growth 2.2-fold, and granulated ash and PK fertiliser 1.7-1.8-fold compared to the control over the 15 years.…”
Section: Discussionsupporting
confidence: 85%
“…For example, Moilanen et al (2012) reported a 3-fold growth increase following loose ash fertilisation after only 10 years at an N-rich drained peatland site. Moilanen et al (2004Moilanen et al ( , 2015 also found that in N-rich pine peatland, ash fertilisation more than doubled stand growth in 15-26 years. All the previous results (Moilanen et al 2002(Moilanen et al , 2004 suggest that with a high peat N concentration like this study's Kannus site, the impact of ash fertilisation on tree growth will exceed the 15-year study period.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Wood ash is considered even better than the commercial fertilizers because of slower nutrient release. Moilanen (2015) concludes that wood ash fertilization is economically feasible and already during commercial thinning annual income was three times higher than in control (Moilanen et al, 2015). Studies in Latvia also reveal that ash fertilization on drained organic soil induced additional volume increment from 2 to almost 5 m 3 ha -1 per year (Okmanis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing demand and removals of biomass require to improve the tree growth conditions, for example, by proper thinning, amelioration and other forestry operations, however productivity of forest stands can be significantly increased by fertilization [1][2][3]. Another issue related to biomass consumption is utilization of wood ash, which so far is mostly considered as waste.…”
Section: Introductionmentioning
confidence: 99%